Energiemanagement-Strategien für batterieelektrische Fahrzeuge - Suchaneck, André (Forschungsberichte aus der Industriellen Informationstechnik / Institut für Industrielle Informationstechnik (IIIT), Karlsruher Institut für Technologie, 2018)
The energy management of battery electric vehicle is important for maximum utilisation of the battery. This book elaborates the requirements of the energy management and defines them as mathematical optimization problem. Strategies for the development process based on dynamic programming and for driving operation based on Pontryagin's maximum principle are presented to consider all significant influences.